STUDY OF PLANT ROOT TURTLE DRYOPTERIS CRASSIRHIZOMA NAKAI - Aguirre M., R. (2013)
It was worked with the plant - fruit and peel Raíz de tortuga, “Dryopteris crassirhizoma nakai” in Junín Department, Chanchamayo province, Pichanaki district. This plant is used to stomache caused by parasites and to stopped hemorroids. The objective of this research was to determine in the first its content of potassium, calcium and metabolites responsible of its use. Qualitative, quantitative analysis and a phytochemical study in peel and fruit was realized. It was determined presence of nutrients in macro and micro amounts, was found calcium 3,7% in peel and 4,22% in fruit, potassium 3789 ppm in peel and 4697 ppm in fruit, presence of, strontium, antimony, among others in ashes. It was determined presence of phenols, triterpens, coumarins, flavonols and alkaloids by phitochemical screening.